Increased accuracy of a novel mRNA‐based urine test for bladder cancer surveillance. (12th October 2017) - Pichler, Renate; Fritz, Josef; Tulchiner, Gennadi; Klinglmair, Gerald; Soleiman, Afschin; Horninger, Wolfgang; Klocker, Helmut; Heidegger, Isabel
Abstract : Objectives: To evaluate the diagnostic accuracy of the Xpert Bladder Cancer (BC) Monitor, compared with cystoscopy and cytology in the oncological follow‐up of non‐muscle‐invasive bladder cancer (NMIBC). Material and Methods: A total of 140 patients with a history of NMIBC undergoing routine surveillance at our institution were enrolled prospectively in this study (ISRCTN study registry number 37210907). Urine cytology was evaluated according to the Paris classification system. In addition, urinary specimens were analysed using the Xpert BC Monitor, which measures five target mRNAs (ABL1, CRH, IGF2, UPK1B, ANXA10) using real‐time PCR. Descriptive analysis, diagnostic accuracy including sensitivity, specificity, positive (PPV) and negative predictive value (NPV), receiver‐operating characteristic curve, and area under the curve (AUC) were calculated. Results: The overall sensitivity (0.84) and NPV (0.93) of the Xpert BC Monitor were significantly superior to those of bladder washing cytology (0.33 and 0.76; P < 0.001). Subgroup analyses confirmed the high sensitivity of the Xpert BC Monitor even in low‐grade (0.77) and pTa (0.82) disease compared with barbotage cytology (low‐grade: 0.13; pTa: 0.21). The overall specificity of the Xpert BC Monitor and barbotage cytology was similar (0.91 vs 0.94; P = 0.41). Combining the Xpert BC Monitor with barbotage cytology (AUC = 0.85) did not enhance diagnostic performance compared with the performance of the Xpert BC Monitor alone (AUC = 0.87). Conclusion: In this study, we report for the first time that the Xpert BC Monitor, a new mRNA‐based urine test, outperforms cytology with regard to sensitivity and NPV, even in low‐grade and pTa tumours, with no reduction of specificity.